Pengaruh Manajemen Hutang, Piutang, Persediaan, terhadap Profitabilitas dengan Arus Kas sebagai Variabel Intervening Pada Perusahaan Sektor Kesehatan yang terdaftar BEI - Karina Sekar Rachmadanti; Slamet Riyadi (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
This Research Has The Purpose Of Analyzing The Effect Of Debt Management, Receivables Management, And Inventory Management On Company Profitability With Cash Flow As An Intervening Variable. The Techniques Applied Include Quantitative Descriptive Research Design, With Statistics Taken Through The Annual Reports Of Health Sub-Sector Companies Listed On The Stock Exchange! Indonesia During The Period Of 2019 To 2022. The Research Population Consists Of 12 Companies, With Samples Obtained By The Purposive Sampling Method, So That 5 Companies Are Obtained For The Object Of The Research. The Research Results State That Inventory Management Has A Significant Influence On Profitability, While Debt Management And Receivables Management Do Not Show A Significant Influence On Profitability Or Cash Flow. In Addition, Cash Flow Does Not Work As A Significant Intervening Variable In The Relationship Between Debt, Receivable, And Inventory Management On Profitability. This Finding Indicates That Efficient Inventory Management Can Improve Cash Flow And, In Turn, Contribute To The Company's Profitability. However, Less-Off Debt And Receivable Management Can Hinder The Company's Profit Potential. This Research Provides Important Implications For Company Management In The Health Sub-Sector To Focus More On Inventory And Cash Flow Management To Improve Financial Performance. In Addition, The Results Of This Research Also Show The Need For A More Holistic Strategy In Financial Management, Which Does Not Only Focus On One Aspect, But Also Integrates Debt, Receivable, And Inventory Management Effectively. Thus, Companies Can Achieve Better And Sustainable Profitability In The Future.